The major outer sheath protein forms distinct conformers and multimeric complexes in the outer membrane and periplasm of Treponema denticola. Issue 1 (December 2017) - Puthenveetil, Robbins; Kumar, Sanjiv; Caimano, Melissa; Dey, Abhishek; Anand, Arvind; Vinogradova, Olga; Radolf, Justin
Abstract The major outer sheath protein (MOSP) is a prominent constituent of the cell envelope ofTreponema denticola (TDE) and one of its principal virulence determinants. Bioinformatics predicts that MOSP consists of N- and C-terminal domains, MOSPN and MOSPC . Biophysical analysis of constructs refoldedin vitro demonstrated that MOSPC, previously shown to possess porin activity, forms amphiphilic trimers, while MOSPN forms an extended hydrophilic monomer. In TDE andE. coli expressing MOSP with a PelB signal sequence (PelB-MOSP), MOSPC is OM-embedded and surface-exposed, while MOSPN resides in the periplasm. Immunofluorescence assay, surface proteolysis, and novel cell fractionation schemes revealed that MOSP in TDE exists as outer membrane (OM) and periplasmic trimeric conformers; PelB-MOSP, in contrast, formed only OM-MOSP trimers. Although both conformers form hetero-oligomeric complexes in TDE, only OM-MOSP associates with dentilisin. Mass spectrometry (MS) indicated that OM-MOSP interacts with proteins in addition to dentilisin, most notably, oligopeptide-binding proteins (OBPs) and the β-barrel of BamA. MS also identified candidate partners for periplasmic MOSP, including TDE1658, a spirochete-specific SurA/PrsA ortholog. Collectively, our data suggest that MOSP destined for the TDE OM follows the canonical BAM pathway, while formation of a stable periplasmic conformer involves an export-related, folding pathway not present inE. coli .